TRADD Mediates RIPK1-Independent Necroptosis Induced by Tumor Necrosis Factor - Wang, Lili; Chang, Xixi; Feng, Jinli; Yu, Jiyun; Chen, Guozhu (Frontiers in Cell and Developmental Biology, 2020)
As a regulated form of programmed cell death, necroptosis has the intrinsic initiators, including receptor-interacting serine/threonine-protein kinase 1 (RIPK1), RIPK3 and mixed-lineage kinase domain-like protein (MLKL), which combine to form necroptotic signaling pathway and mediate necroptosis induced by various necroptotic stimuli, including tumor necrosis factor (TNF). Although chemical inhibition of RIPK1 blocks TNF-induced necroptosis, genetic elimination of RIPK1 does not suppress but facilitate necroptosis triggered by TNF. Moreover, RIPK3 has been reported to mediate the RIPK1-independent necroptosis, but the involved mechanism is unclear. In this study, we found that TRADD was essential for TNF-induced necroptosis in RIPK1-knockdown L929 cells. Mechanistic study demonstrated that TRADD bound RIPK3 to form new protein complex, which then promoted RIPK3 phosphorylation via facilitating RIPK3 oligomerization, leading to RIPK3-MLKL signaling pathway activation. Therefore, TRADD acted as a partner of RIPK3 to initiate necroptosis in RIPK1-knockdown L929 cells in response to TNF stimulation. In addition, TRADD was critical for the accumulation of reactive oxygen species, which contributed to RIPK1-independent necroptosis triggered by TNF. Collectively, our data demonstrate that TRADD acts as the new target protein for TNF-induced RIPK3 activation and the RIPK1-indepdentdent necroptosis.